Distribution and ecology of polar cod (Boreogadus saida) in the eastern Barents Sea: A review of historical literature. (April 2021) - Aune, Magnus; Raskhozheva, Evgeniia; Andrade, Hector; Augustine, Starrlight; Bambulyak, Alexei; Camus, Lionel; Carroll, JoLynn; Dolgov, Andrey V.; Hop, Haakon; Moiseev, Denis; Renaud, Paul E.; Varpe, Øystein
Abstract: The polar cod ( Boreogadus saida ) has a circumpolar distribution and is the most abundant planktivorous fish in the Arctic. Declining sea-ice coverage impacts polar cod directly and also facilitates expansion of human activities in the region leading to increasing anthropogenic pressures on biota. Here we summarize current data and knowledge on polar cod from the Russian sector of the Barents Sea and discuss knowledge needs for the management of polar cod under changing environmental conditions and anthropogenic impacts. We review 36 Russian historical (1935 - 2020) sources of data and knowledge largely unknown to western researchers, in addition to sources already published in the English language. This effort allowed for digitalization and visualization of 69 separate datasets on polar cod ecology, including maturation, fertility, feeding intensity, diet, lipid content, length-weight relationships and seasonal variation in larval size. Our review suggests that polar cod abundances are particularly large in the eastern Barents Sea and adjacent waters. Here, we identify and discuss key knowledge gaps. The review of polar cod in the eastern Barents Sea revealed 1) major variation in the timing and area of polar cod spawning, 2) uncertainty as to what degree the polar cod is dependent on sea ice, 3) deficient knowledge of juvenile (e.g., 0-group) distributions, particularly in the north-eastern Barents Sea, 4) deficient knowledge of the species' genetic structure and spatio-temporal distributions, and 5) insufficient understanding as to whether ongoing environmental change may induce phenological changes affecting the availability of potential food items for polar cod larvae and their match in space and time. Filling these knowledge gaps would provide an important step towards the reliable knowledge base needed in order to perform well-founded management and impact assessment under environmental changes and increasing anthropogenic impacts. Highlights: The polar cod ( Boreogadus saida ) is a key Arctic fish species. Increased environmental and anthropogenic impact calls for updated knowledge. A synthesis of historical sources allowed for identification of knowledge gaps. Aspects of genetics, spawning, larval ecology and distributions are poorly known. There is uncertainty as to what degree the polar cod is dependent on sea ice.